D'une auto-prescription à une mise en œuvre d'investigation. Étude de cas en SVT au collège - Maryline Coquidé; Estelle Flatter (Nantes Université, 2015)
To contribute to better knowledge of the factors that influence the workings and implementations of inquiry based teaching, we propose a case study of four biology teachers at middle school. Preliminary interviews were conducted, class sessions were recorded and stimulated records (Clot 2001) were made. The analyses of the corpus show representations of the investigations, on the roles of the teacher and of students. The interviews show the importance of curricular aspect, concerning the content and resources, material resources, time constraints and pedagogical aspects. Two specific analysis on the balance between guidance by the teacher and student autonomy on the one hand , the link between teachers establish investigative approaches and complex tasks on the other hand, are used to study the influence of national and regional curricula.